MSL in the digital ages: Effects and effectiveness of computer-mediated intervention for FL learners with dyslexia - Pfenninger, Simone E. (Studies in Second Language Learning and Teaching, 2015)
The longitudinal intervention study reported here is the first to investigate the efficiency of computer learning software specifically designed for dyslexic Swiss German learners of Standard German as a second language (L2) and English as a third language (L3). A total of 40 subjects (20 of them dyslexics and 20 of them nondyslexics; 10 students from each group participated in in- terventions and the other 10 from each group served as control groups) were assessed with a battery of verbal and written pre- and posttests involving pho- nological/orthographic and semantic measures of their L2 and L3 before and after three months of daily intervention with the software. The results show that computer-based training in the L3 is potentially an important tool of intervention for dyslexic students as it has a positive effect on the components of L3 as well as L2 learning. As a consequence of their progress in acquiring the relationships between L3 graphemes and phonemes, the experimental groups, but not the control groups, made significant gains on L2 naming accuracy and speed, L2 and L3 word reading, L2 and L3 phonological awareness, and L2 and L3 receptive and productive vocabulary and comprehension tasks.